Validation and assessment of the arabic psychological first aid scale among physicians, nurses, and counselors in Jordan - Basma Eid Alshareef; Othman A. Alfuqaha; Ibraheem B. Maali; Khaled Amer (BMC Psychology)
Abstract Background Psychological first aid (PFA) involves strategies to tackle problems that occur as a result of disasters. This study aimed to validate the Arabic version of PFA scale through validity (face, content, convergent, discriminant validity, and confirmatory factor analysis) and reliability (Cronbach’s alpha). Furthermore, it aimed to assess the perceived levels of knowledge, skills, and attitudes of PFA among healthcare providers (HCPs). Moreover, it determined the differences between HCPs based on their knowledge, skills, and attitudes of PFA. Methods A sample size of 389 HCPs (physicians = 68, nurses = 173, and counselors = 148) was conveniently selected to participate during the period of 10 December 2023 to 10 February 2024 after completing the translated PFA scale into the Arabic language. Descriptive, translation, validation process, and reliability were conducted. Results The translation process was satisfied. The content validity index was 0.91, yielding proper clarity of items. Three constructs were loaded with a total variation of 63.43%, indicating a proper model fit. The goodness-of-fit indices for the PFA model revealed that relative chi-square was 1.47, comparative fit index was 0.91, Tucker-Lewis index was 0.89, and the root mean square of error approximation was 0.046. Cronbach alpha values for knowledge, skills, and attitudes of PFA were 0.90, 0.89, 0.87, respectively. We found that counselors have more knowledge (64.4%), skills (73.4%), and attitudes (73.4%) compared to physicians and nurses. There are significant differences (p < 0.001) between the selected HCP groups, particularly for the counselors’ group in terms of knowledge, skills, and attitudes of PFA. Conclusions The Arabic PFA scale is valid and reliable among HCPs. The results highlight the emergent need to provide knowledge, skills, and attitudes of PFA interventions among medical professionals, particularly for physicians and nurses. The Arabic version of PFA helps all HCPs in Arab countries to assess, apply, and implement PFA interventions.